2017
DOI: 10.18203/2349-3291.ijcp20174756
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric appendicitis score in the diagnosis of childhood appendicitis: a validation study

Abstract: Background: Pediatric appendicitis score (PAS) is a scoring system which includes symptoms, physical examination and laboratory tests in children suspected to have appendicitis. The objectives of this study were to analyze the diagnostic value of Paediatric Appendicitis Score and to aid early diagnosis of appendicitis.Methods: A prospective study was done in a Medical College hospital, in Mangalore in children aged between 4-16 years, admitted during study period June to December 2016, with right Iliac fossa p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…The average time of symptom evolution in patients with complicated appendicitis was 47.7 hours, longer than in patients with uncomplicated appendicitis. This is consistent with other authors, who state that more than 60% of patients with complicated appendicitis have symptoms of more than 72 hours of evolution (8,15).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The average time of symptom evolution in patients with complicated appendicitis was 47.7 hours, longer than in patients with uncomplicated appendicitis. This is consistent with other authors, who state that more than 60% of patients with complicated appendicitis have symptoms of more than 72 hours of evolution (8,15).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the average number of leukocytes in the initial hemogram was high for the age ranges, which would suggest the usefulness of scales such as the pediatric score (PAS) (8) in our environment. The criteria of these scales indicate that a leukocyte count greater than 10,000 cells/mm 3 may increase the diagnostic probability of appendicitis (8,9). Creactive protein was tested in just over half the population.…”
Section: Discussionmentioning
confidence: 50%
“…Recently Parveen and colleagues validated PAS scores by evaluating ultrasound findings and histopathology report. 20 Another study also documented that PAS≥7 was strongly indicative of appendicitis and reported rate of negative appendectomy as 0%. 21 A local study showed that Alvarado score of 6 or more has a diagnostic accuracy of 82.9% in predicting acute appendicitis in children.…”
Section: Discussionmentioning
confidence: 97%
“…Children rarely show symptoms of appendicitis symptoms that are typical of adults, this causes challenges for medical personnel, especially doctors. to make a timely diagnosis (Parveen KZ et al, 2017). To assist in establishing a diagnosis of acute appendicitis in children, there is a scoring system that has been proposed and until now the Pediatric Appendicitis Score (PAS) has been used.…”
Section: Discussionmentioning
confidence: 99%
“…Good correlation was also found between PAS assessment and biopsy results, but no correlation was found good between PAS and USG results, and this study concludes that PAS is an assessment tool for diagnosing appendicitis. (Parveen KZ et al, 2017).…”
Section: Discussionmentioning
confidence: 99%